Temporal and spatial variation of potassium balance in agricultural land at national and regional levels in China - Liu, Yingxia; Ma, Jinchuan; Ding, Wencheng; He, Wentian; Lei, Qiuliang; Gao, Qiang; He, Ping (PloS one, 2017)
Linking potassium (K) balance to soil fertility creates a valuable indicator for sustainability assessment in agricultural land-use systems. It is crucial for the efficient use of K resources, food security and resource sustainability to realize soil K balance status in China. Therefore, temporal and spatial changes of K balance for farmland in China from 1980 to 2015 were analyzed at national and regional levels using statistical data and related parameters. At the national scale, K input increased from 6.78 Mt K2O in 1980 to 23.44 Mt K2O in 2015 with an average annual increment of 0.48 Mt K2O, and output changed from 8.10 Mt in 1980 to 21.31 Mt in 2015 with an average annual increment of 0.38 Mt K2O as well. On average, K balance was -24.17, -5.92, 21.31 and 19.50 kg K2O ha-1 in 1980s, 1990s, 2000s and 2010s, respectively. Moreover, the average balance of six regions was considerably different which were -21.37, 1.25, 13.70, -22.79, 99.22 and 7.18 kg K2O ha-1 from 1980 to 2015. The potassium use efficiency (KUE) decreased with time which were 127.09, 104.35, 87.69 and 89.69% in 1980s, 1990s, 2000s and 2010s, respectively, and the decline of slope could also reflect the variation tendency of KUE. Great variation of K balance across different regions demonstrated that fertilizer application and management practices need to be adjusted to local conditions.